A Multipolar World: A Modern Political Agenda - Aslanbek H. Denilkhanov (RUDN Journal of Political Science)
Liberal values, developed by Western ideology and political science for three centuries, formed the methodological basis in the politics of many countries, which are focused on freedom and democracy, in solving complex socio-political and political-philosophical problems. On their basis, the collective West built a unipolar world with the unconditional hegemony of certain ideological attitudes. Due to the exhaustion of these attitudes today and the lack of new ones that could support the dominant position of Western countries in the international arena, an information war is being waged against countries that have chosen a political vector based on other value grounds, with all the ensuing consequences, up to armed clashes. In modern conditions of the global trend towards multipolarity, alliances of states are being created, focused on preserving self-identity and constructive dialogue with all those who recognize it. The objective reasons for this trend are primarily due to the globalization processes taking place in the global economy. Due to the development of logistics technologies, it naturally became necessary to develop new forms of cooperation. One of the ways of such regulation of relations has long been the unification into associations, alliances, unions, etc. In this regard, for Russia, a transcontinental state that partially occupies the territories of Europe and Asia, the most promising strategic direction is the paradigm of Eurasianism, which has a century-old history, the main goal of which is the harmonization of interregional relations. The article draws a parallel between the thinkers of Eurasianism - a worldview movement that arose among Russian emigration at the beginning of the last century - and modernity in order to develop the most acceptable political guidelines in a rapidly changing globalized world based not only on the economic strategies of states, but also on common basic cultural values.